2015
DOI: 10.1103/physrevc.92.024907
|View full text |Cite
|
Sign up to set email alerts
|

Energy loss, hadronization, and hadronic interactions of heavy flavors in relativistic heavy-ion collisions

Abstract: We construct a theoretical framework to describe the evolution of heavy flavors produced in relativistic heavy-ion collisions. The in-medium energy loss of heavy quarks is described using our modified Langevin equation that incorporates both quasi-elastic scatterings and the medium-induced gluon radiation. The space-time profiles of the fireball is described by a (2+1)-dimensional hydrodynamics simulation. A hybrid model of fragmentation and coalescence is utilized for heavy quark hadronization, after which th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(145 citation statements)
references
References 122 publications
(129 reference statements)
4
141
0
Order By: Relevance
“…The two last models also include scattering of D mesons in the hadronic phase of the medium. Also for the Cao, Qin, Bass model, the hadronic-rescattering effects have been studied in a recent publication [84] and no large differences in the R AA are observed, when these processes are considered.…”
Section: Comparison With Modelsmentioning
confidence: 99%
“…The two last models also include scattering of D mesons in the hadronic phase of the medium. Also for the Cao, Qin, Bass model, the hadronic-rescattering effects have been studied in a recent publication [84] and no large differences in the R AA are observed, when these processes are considered.…”
Section: Comparison With Modelsmentioning
confidence: 99%
“…It is suggested that the analysis of the azimuthal angular correlation might provide information on the energy loss mechanism of heavy quarks in the QGP [71] because stronger interactions should result in less pronounced angular correlations. Since in the PHSD we can follow up the fate of an initial heavy quark-antiquark pair throughout the partonic scatterings, the hadronization and final hadronic rescatterings, the microscopic calculations allow to shed some light on the correlation between the in-medium interactions and the final angular correlations.…”
Section: Azimuthal Angular Correlationsmentioning
confidence: 99%
“…The nuclear modification factors of D mesons and non-prompt J/ψ are also described by a model calculation by the Duke group [61], that includes radiative and collisional energy loss within an hydro-dynamical medium and performs the hadronization of heavy quarks using recombination and fragmentation.…”
Section: Jhep11(2015)205mentioning
confidence: 99%